Math, asked by gayatribiradar682, 10 months ago

Please Solve This....​

Attachments:

Answers

Answered by Anonymous
2

Solution:-

 \rm \: {x}^{2}  - 5x + 4 = 0

 \rm \: sum \: of \: the \: zeroes \:  =   - \dfrac{cofficient \: of \: x}{cofficient \: of \: x {}^{2} }

 \rm \: product \: of \: zeroes \:  =  \dfrac{constant \: term \: }{cofficient \: of \: x {}^{2} }

 \alpha  +  \beta  =  \dfrac{ - ( - 5)}{1}

 \alpha  \beta  =  \dfrac{4}{1}

 \rm \:  \alpha  +  \beta  = 5

 \alpha  \beta  = 4

Now take

 \rm \:  \dfrac{1}{ \alpha }  +  \dfrac{1}{ \beta }  - 2 \alpha  \beta

Now simply

 \rm \:  \dfrac{ \beta  +  \alpha }{ \alpha  \beta }  - 2 \alpha  \beta

Put the value

 \dfrac{5}{4}  - 2 \times 4

 \rm \:  \dfrac{5}{4}  - 8

 \dfrac{5 - 8 \times 4}{4}

 \dfrac{5 - 32}{4}

 \to \dfrac{27}{4}

Answered by Anonymous
3

Step-by-step explanation:

please follow me back I will follow you

please!!!

Similar questions